2017
DOI: 10.1021/jacs.7b01594
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Effects of Gating on the Ion Occupancy of the K+ Channel Selectivity Filter Using Two-Dimensional Infrared Spectroscopy

Abstract: The interplay between the intracellular gate and the selectivity filter underlies the structural basis for gating in potassium ion channels. Using a combination of protein semisynthesis, two-dimensional infrared (2D IR) spectroscopy, and molecular dynamics (MD) simulations, we probe the ion occupancy at the S1 binding site in the constricted state of the selectivity filter of the KcsA channel when the intracellular gate is open and closed. The 2D IR spectra resolve two features, whose relative intensities depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 62 publications
(133 reference statements)
0
41
0
Order By: Relevance
“…This overzealous scientific attention is based on its' role in catalyzing an unparalleled rapid and highly ion-selective transport. The molecular mechanism underlying this unique function has been the subject of functional, structural, and computational studies and yet remains a controversial topic of research (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This overzealous scientific attention is based on its' role in catalyzing an unparalleled rapid and highly ion-selective transport. The molecular mechanism underlying this unique function has been the subject of functional, structural, and computational studies and yet remains a controversial topic of research (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16).…”
mentioning
confidence: 99%
“…Despite substantial experimental evidence and computational studies supporting these 2 different mechanistic proposals, a clear consensus is yet to be reached regarding the universality of a model for ion conduction in K + channels. As a result, this topic has reemerged as highly controversial (7)(8)(9)19).…”
mentioning
confidence: 99%
“…Conversely, the complexity observed in permeation features (i.e., low open probability for K + and very diminished inactivation in the presence of Rb + or Cs + ) cannot be explained just in terms of binding at equilibrium and likely relates to reported differences in the occupancy of the S2 and S3 sites by the permeant cations and/or kinetics contributions. In addition, some recent experiments performed by 2D-IR spectroscopy found that the occupation of the S1 site diminishes upon channel opening [63].…”
Section: Ion Binding To the Kcsa Selectivity Filter And Modulation Bymentioning
confidence: 96%
“…We not only provide new experimental evidence that support the knock-on model of ion conduction but also present new spectroscopic signatures for a Val76-flipped state which has only been observed in simulations. Our second study focuses on the coupling between the selectivity filter and the helix bundle gate, inferred through changes in the ion occupancy of the filter under different experimental conditions [34]. Using the same techniques, we probed the ion occupancies in the selectivity filter of KcsA in the closed-constricted and the open-constricted states.…”
Section: Objectivementioning
confidence: 99%
“…While the details of the MD simulations are provided elsewhere [33,34]. Briefly, for our initial studies, we performed MD simulations using Drude oscillator derived polarizable force fields starting from previously described equilibrated structures [38].…”
Section: Simulations and 2d Ir Calculationsmentioning
confidence: 99%